2007
DOI: 10.1007/s10659-007-9147-8
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation Formulas for Polarization Ratio and Phase Shift of Rayleigh Waves in Prestressed Anisotropic Media

Abstract: This paper completes an earlier study (Tanuma and Man, Journal of Elasticity, 85, 21-37, 2006) where we derive a first-order perturbation formula for the phase velocity of Rayleigh waves that propagate along the free surface of a macroscopically homogeneous, anisotropic, prestressed half-space. We adopt the formulation of linear elasticity with initial stress and assume that the deviation of the prestressed anisotropic medium from a suitably-chosen, comparative, unstressed and isotropic state be small. No as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Similar conclusions are reported in Ref. 11, where a perturbation approach is applied to consider an arbitrary state of surface stress. The literature on Lamb wave polarization is relatively more sparse and mostly limited to analytical and numerical studies.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar conclusions are reported in Ref. 11, where a perturbation approach is applied to consider an arbitrary state of surface stress. The literature on Lamb wave polarization is relatively more sparse and mostly limited to analytical and numerical studies.…”
Section: Introductionsupporting
confidence: 86%
“…[4][5][6] Investigations of Rayleigh waves polarization, for example, have studied its relation to the state of stress of a surface. [7][8][9][10][11] Specifically, the numerical investigation of Junge et al 10 have shown that surface stress has a much stronger effect on polarization than on phase velocity. Similar conclusions are reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…the methods in Sections 6 and 7 of Tanuma & Man (2002), Sections 6 and 7 of Tanuma & Man (2008), and Section 4 of Tanuma et al (2013)): …”
Section: Surface Impedance Matrix Of Weakly-anisotropic Homogeneous Ementioning
confidence: 99%
“…We will write ζ 22 , ζ 33 and ζ 23 − ζ 23 appearing in Equation (31) in terms of the entries of the matrices in (44) and the components Z ij in the formula (29). From (29) and (43) it follows that To investigate the effects of T • and A on the quantities above, we will look carefully at the components r 22 , r 33 and t 23 to show that the effects of T • and A on them come only from a 22 , a 23 , a 33 , a 44 and T • 22 , which proves the lemma.…”
Section: A Necessary and Sufficient Condition For The Existence Of Ramentioning
confidence: 99%